THE EFFECT OF PRICE AND BRAND TRUST ON CUSTOMER RETENTION AT NATASHA SKIN CARE MANADO - Kembuan, Fleyti Onecia (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Human needs to look more attractive and youthful it is a way of life since the days of the beginning of human civilization. The human desire to look attractive becomes one of the basic human needs in addition to food, clothing, and shelter. The study aims to address the effect of price and brand trust on consumer at Natasha Skin Care Manado. 89 customers of Natasha Skin Care Manado were surveyed as respondents. The result show that variable price and brand trust have significant effect on customer retention simultaneously, also price has significant and positive effect on customer retention partially and brand trust also have significant and positive impact to customer retention. As the recommendation, the company must give attention to the marketing strategy of company, especially to the variable price and brand trust, because this variable has impact to the customer retention. Keywords: price, brand trust and customer retention